Establishment of a standard wet coffee processing for Makilala, North Cotabato microclimate conditions and assessing the coffee drink thereof - Go,Samuel P. (2010)
This study was counducted to establish a standardized wet coffee processing for Makilala, North Cotabato based on a usual wet process done by a Makilala farmer and under the microcalimate conditions of the area. The coffee obtained from the standardized wet process was assessed of its sensory qualities snd tested for the degree of difference from the control using Difference from the Control Sensory Evaluation. Three fermentation times were tested -24, 48 and 72 hours using Coffee arabica var. catimor. The 48-hour sample showed the highest amount of lactic acid bacteria present. Difference from the control test was used to determine if the three samples varied from the control in the overall sensory attributes. By subjecting the results to analysis of variance, significant difference was observed in the overall sensory attributes of all samples. Pairwise comparison of means showed that the 72-hour sample was the most varied of all. Wet processing the coffee beans for 48 hours is the best choice to obtain a high quality roasted coffee drink.